(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
Tourism and the environment are closely interlinked: while the environment serves as a major asset for attracting tourists, tourism itself can have both beneficial and detrimental impacts on natural ecosystems. This article explores the complex, bidirectional relationship between the environment and tourism. It provides a comprehensive review of current literature, describes applied methodologies, and offers insights drawn from international case studies. The results reveal how environmental quality directly influences tourist satisfaction and economic sustainability. Based on the findings, this paper presents practical recommendations for policymakers, tourism planners, and environmental stakeholders to foster sustainable tourism that preserves ecological integrity while supporting economic growth.